Socio-Economic Poverty among Yoruba Women in Nigeria: A Qualitative Analysis of Structural and Cultural Determinants - Michael Olajide (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This study examines socio-economic poverty among Yoruba women in the Southwestern region of Nigeria, with women as the main unit of analysis and Yorubaland as the socio-cultural context of the study. The aim of this study is to identify the structural, cultural, and economic factors that contribute to the sustainability of Yoruba women's socio-economic poverty and to examine their implications for women's empowerment and national development. This research employs a qualitative approach, utilizing a critical analysis of academic literature, policy documents, and secondary data from international development agency reports, complemented by contextual observations of the socio-economic realities of the Yoruba people. The findings of the study show that the socio-economic poverty of Yoruba women is influenced by limited access to education, patriarchal cultural norms, economic inequality, government policies that are less favorable to women, the high cost of living, and lack of access to financial resources. These factors collectively limit women's economic participation, inhibit asset accumulation, and reinforce cycles of dependency and vulnerability. The study also found that unpaid domestic work and the exclusion of women from the decision-making process weakened their socio-economic progress. This article contributes to the study of gender and development by presenting a contextual analysis of women's poverty in Yoruba society and affirms the urgency of gender-sensitive policies as a sustainable development strategy in Nigeria.